Comparison of intravascular and surgical treatment of ruptured intracranial aneurysms: A literature review - Jakub Bartoszewicz; Anna Gorajek; Małgorzata Kudan; Aleksandra Osiejewska; Anna Grądzik; Karolina Mikut; Dominika Wojtachnio; Izabela Nowakowska (Kazimierz Wielki University, 2022)
Introduction and purpose: Ruptured intracranial aneurysm causes a life-threatening subarachnoid hemorrhage, which is characterized by a high percentage of disability and mortality. As of today, we have two main treatments for this condition: microsurgical clipping and endovascular coil embolization. The aim of the study was to evaluate both treatment modalities, assess their limitations and compare them in terms of mortality, postoperative condition/complications and long-term patient's condition Materials and methods: This study was based on the analysis of medical databases' analysis. Results: Four randomized controlled trials, one guideline and one meta-analysis were reviewed. The results did not significantly differ between the studies. They proved that endovascular coiling technique showed fewer poor outcomes, deaths or dependency, one year after the treatment. These differences decreased in the following years. The microsurgical clipping was more effective at total obliteration of the aneurysm but was not related to better quality of life for those patients. Both techniques also did not differ in terms of the patients' distant long-term neuropsychological state. Conclusion: Endovascular coiling embolization is still a rapidly developing technique that may be the main treatment modality in the future. However, at this point, both treatments have advantages and limitations. It is crucial to assess every patient individually.